First record of Xylosandrus compactus (Coleoptera: Curculionidae: Scolytinae) on cocoa in Peru. (2017)
The weevil Curculionidae Scolytinae Xylosandrus compactus is a polyphagous invasive pest native to Asia. It is now found in tropical and subtropical areas of all continents. The insect probably entered South America in the 1970s, where it was first detected in 1973 in Peru and then detected in the Peruvian Amazon in 1991. This paper is the first report of it on cacao in the Peruvian Amazon, where it is causing serious damage to cocoa nurseries. Several control methods are proposed.